2001
DOI: 10.1046/j.0953-816x.2001.01574.x
|View full text |Cite
|
Sign up to set email alerts
|

Amphetamine and cocaine induce different patterns of c‐fos mRNA expression in the striatum and subthalamic nucleus depending on environmental context

Abstract: In the dorsal striatum, there are two major populations of medium spiny projection neurons. One population is positive for dynorphin mRNA (DYN+), and these cells project preferentially to the substantia nigra, forming the so-called 'direct pathway'. A second population is positive for enkephalin mRNA (ENK+), and these cells influence the substantia nigra indirectly, via the globus pallidus and subthalamic nucleus. Psychostimulant drugs, such as amphetamine and cocaine, are reported to induce immediate early ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
101
2

Year Published

2003
2003
2010
2010

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(110 citation statements)
references
References 62 publications
7
101
2
Order By: Relevance
“…Since this activation has consequences at the gene level, adenosine could selectively facilitate plastic changes in the synapses of the GABAergic enkephalinergic neurons, which can have implications for drug therapy in neuropsychiatric disorders and drug abuse. For instance, there is experimental evidence for the existence of selective gene expression in GABAergic enkephalinergic neurons during sensitization to the behavioral effects of psychostimulants (Uslaner et al, 2001). In fact, genetic inactivation of A 2A receptors has been reported to attenuate amphetamineinduced behavioral sensitization (Chen et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Since this activation has consequences at the gene level, adenosine could selectively facilitate plastic changes in the synapses of the GABAergic enkephalinergic neurons, which can have implications for drug therapy in neuropsychiatric disorders and drug abuse. For instance, there is experimental evidence for the existence of selective gene expression in GABAergic enkephalinergic neurons during sensitization to the behavioral effects of psychostimulants (Uslaner et al, 2001). In fact, genetic inactivation of A 2A receptors has been reported to attenuate amphetamineinduced behavioral sensitization (Chen et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that manipulating factors such as dose, the environmental context surrounding drug administration, and drug history can strongly influence which striatofugal circuits are engaged by psychostimulant drugs (Badiani et al, 1999;Uslaner et al, 2001Uslaner et al, , 2003a. For example, psychostimulant administration in a novel test environment produces a dose-dependent increase in c-fos expression in EnkÀ cells compared to novelty alone (Uslaner et al, 2003a, b), and this increase in c-fos expression is maintained following repeated treatment and extended withdrawal (Uslaner et al, 2003a).…”
Section: Morphine Induces a Different Pattern Of Gene Expression In Tmentioning
confidence: 99%
“…By contrast, psychostimulants show a different profile of cfos activation in Enk þ cells. Although high doses of amphetamine (but not cocaine) given in a novel test environment have a similar inhibitory effect on c-fos expression as does morphine (Uslaner et al, 2003a, b), low to moderate doses of either amphetamine or cocaine increase c-fos expression in Enk þ cells (Uslaner et al, 2001(Uslaner et al, , 2003a, an effect that is maintained following repeated treatment and extended withdrawal (Uslaner et al, 2003a).…”
Section: Morphine Induces a Different Pattern Of Gene Expression In Tmentioning
confidence: 99%
See 2 more Smart Citations